SHAPING INTERFAITH PERSPECTIVES: AN ANALYSIS OF INDONESIAN YOUTH VIEWS ON TRUST, SOCIAL INTERACTION, AND POLITICAL INCLINATIONS ACROSS SECONDARY SCHOOL - Fatah, Anton Abdul; Huda, Miftahul (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
The objective of this research is to analyze the viewpoints of young Indonesians during their adolescence and adulthood about trust between different religions, social interaction, and political inclinations. Specifically, it emphasizes how the duration of secondary school education might shape their viewpoints. This study used ordinal logistic regression analysis to examine panel data collected from the Indonesian Family Life Survey, which comprises a sample size of over 20,000 respondents. The findings indicate a decrease in the standard of individuals' interfaith conduct between 2007 and 2014. The research indicates that those who finished secondary school during the New Order era exhibit higher levels of tolerance towards interfaith ideas in comparison to those who completed secondary school during the Reformation era. The disparity might be attributed to the policies of the New Order administration, which prioritized national cohesion and stability while actively opposing religious